Effect of Single and Combined Use of Various Organic Amendments on Wheat Grown over Green Manured Soil: I. Growth and Yield Attributes - Aslam, Muhammad; Khan, Muhammad Ayyaz; Awan, Inayat Ullah; Khan, Ejaz Ahmad; Khan, Ahmad Ali; Jilani, Ghulam (Pakistan Journal of Nutrition, 2011)
This field experiment was undertaken on already green manured soil for comparing the efficiency of various organic manures used as alone and in combination, for wheat production. Organic matter sources/treatments used in the study were: Farm Yard Manure (FYM), Poultry Litter (PL), Press Mud (PM) and Sewage Sludge (SS). The amount of each organic amendments used singly was 20 t/ha, while their combinations had 10 t/ha for each of the two amendments making a total of 20 t/ha in a treatment. The experiment was conducted on wheat cv. Bhakkar 2002 as test crop for two consecutive growing seasons (year 2004-05 and 2005-06). Results revealed that Application of all types of organic materials (FYM, PL, PM and SS) and their combinations improved the growth and yield attributes of wheat significantly over control in both the years. The highest biological and grain yield was obtained with the application of PL alone followed by FYM+PL and PL+PM, with a significant difference among them. Economic analysis revealed that the value of Cost-Benefit Ratio (CBR) was highest with FYM+PL followed by PM+SS and PL+PM. The lowest CBR values were recorded under FYM alone and FYM+SS. This was mainly due to smaller yield increase and additional income with these treatments.